A royal penguin eudyptes schlegeli in the Falkland Islands? - Dehnhard, Nina (2020)
The Royal Penguin Eudyptes schlegeli breeds only on Australia’s Macquarie Island and its nearby islets, about 1 200 km southwest of New Zealand. Vagrant Royal Penguins have been reported elsewhere in Australia, New Zealand and Antarctica. Reports of Royal Penguins from other subantarctic islands, including Heard, Prince Edward and Marion Islands, South Georgia and the Falkland Islands are controversial, as these penguins could also be aberrant Macaroni Penguins E. chrysolophus, and species determination can be difficult because of high variation in facial colour in both species. We discuss here the recent sighting of an apparent immature Royal Penguin on New Island, Falkland Islands. A simultaneously visiting adult male Macaroni Penguin allowed a size comparison between the two individuals. This could be the first documented sighting of a vagrant Royal Penguin in the Neotropical region.